Bank Solvency and Funding Cost : New Data and New Results - Schmitz, Stefan; Sigmund, Michael; Valderrama, Laura (Washington, D.C. : International Monetary Fund, 2017)
This paper presents new evidence on the empirical relationship between bank solvency and funding costs. Building on a newly constructed dataset drawing on supervisory data for 54 large banks from six advanced countries over 2004-2013, we use a simultaneous equation approach to estimate the contemporaneous interaction between solvency and liquidity. Our results show that liquidity and solvency interactions can be more material than suggested by the existing empirical literature. A 100 bps increase in regulatory capital ratios is associated with a decrease of bank funding costs of about 105 bps. A 100 bps increase in funding costs reduces regulatory capital buffers by 32 bps. We also find evidence of non-linear effects between solvency and funding costs. Understanding the impact of solvency on funding costs is particularly relevant for stress testing. Our analysis suggests that neglecting the dynamic features of the solvency-liquidity nexus in the 2014 EU-wide stress test could have led to a significant underestimation of the impact of stress on bank capital ratios.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet